2015
DOI: 10.3390/nu7031644
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Decreases Hepatic Lipogenic Genes in Rats Fasted and Refed on a High Fructose Diet

Abstract: Fasting and then refeeding on a high-carbohydrate diet increases serum and hepatic triacylglycerol (TAG) concentrations compared to standard diets. Fructose is a lipogenic monosaccharide which stimulates de novo fatty acid synthesis. Omega-3 (n-3) fatty acids stimulate hepatic β-oxidation, partitioning fatty acids away from TAG synthesis. This study investigated whether dietary n-3 fatty acids from fish oil (FO) improve the hepatic lipid metabolic response seen in rats fasted and then refed on a high-fructose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Castro et al found that long-term intake of HF significantly increased oleic acid levels in the liver and adipose tissue (de Castro, Cardoso, Calder, Jordão, & Vannucchi, 2015b;de Castro et al, 2015a). Our study revealed a significant increase in serum elaidic acid levels in mice after 8 weeks of drinking with HF water.…”
Section: Discussionsupporting
confidence: 61%
“…Castro et al found that long-term intake of HF significantly increased oleic acid levels in the liver and adipose tissue (de Castro, Cardoso, Calder, Jordão, & Vannucchi, 2015b;de Castro et al, 2015a). Our study revealed a significant increase in serum elaidic acid levels in mice after 8 weeks of drinking with HF water.…”
Section: Discussionsupporting
confidence: 61%
“…The therapeutic effect demonstrated by Z. officinale or omega‐3 is coherent with other studies that evaluated both therapies or their individual components against metabolic syndrome disorders such as type2 diabetes, obesity, IR, and NAFLD. These effects have been studied to be through regulation of lipogenesis, β‐oxidation besides their antioxidant and anti‐inflammatory activity (de Castro, Cardoso, Calder, Jordão, & Vannucchi, ; Huang, Deng, Meng, & Ma, ; Lai et al, ; Li et al, ; Molinar‐Toribio et al, ; Singh, Akanksha, Singh, Maurya, Srivastava, ). Here, we demonstrated a novel pathway by which the therapeutic approaches treat NAFLD by modulation of ER stress proposed to be responsible for NAFLD progression through different mechanisms (Ferré & Foufelle, ; Jo et al, ; Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While EPA and DHA induce PPARα transcription activity of LCFA oxidative genes, they concomitantly accelerate degradation and/or reduce nuclear distribution of SREBP1c and ChREBP. This decreases SREBP1c (213215) and ChREBP (241245) transcription of lipogenic genes which thereby decreases hepatic TAG and NAFLD in human subjects not segregated by FABP1 genotype. Another possibility is suggested by cannabinoid receptor (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, FABP1 (7, 13, 14, 16, 4042) and the nuclear receptors it impacts, i.e. PPARα (41, 42, 47, 246248), SREBP1c (213215), and ChREBP (241245), continue to be current active therapeutic targets for lipid lowering.…”
Section: Discussionmentioning
confidence: 99%